Aurora A Kinase (AURKA) is required for male germline maintenance and regulates sperm motility in the mouse - Lester, William C; Johnson, Taylor; Hale, Ben; Serra, Nicholas; Elgart, Brian; Wang, Rong; Geyer, Christopher B; Sperry, Ann O (Biology of reproduction, 2021)
Aurora A kinase (AURKA) is an important regulator of cell division and is required for assembly of the mitotic spindle. We recently reported the unusual finding that this mitotic kinase is also found on the sperm flagellum. To determine its requirement in spermatogenesis, we generated conditional knockout animals with deletion of the Aurka gene in either spermatogonia or spermatocytes to assess its role in mitotic and postmitotic cells, respectively. Deletion of Aurka in spermatogonia resulted in disappearance of all developing germ cells in the testis, as expected, given its vital role in mitotic cell division. Deletion of Aurka in spermatocytes reduced testis size, sperm count, and fertility, indicating disruption of meiosis or an effect on spermiogenesis in developing mice. Interestingly, deletion of Aurka in spermatocytes increased apoptosis in spermatocytes along with an increase in the percentage of sperm with abnormal morphology. Despite the increase in abnormal sperm, sperm from spermatocyte Aurka knockout mice displayed increased progressive motility. In addition, sperm lysate prepared from Aurka knockout animals had decreased protein phosphatase 1 (PP1) activity. Together, our results show that AURKA plays multiple roles in spermatogenesis, from mitotic divisions of spermatogonia to sperm morphology and motility.